2016
DOI: 10.2500/ajra.2016.30.4280
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-life Outcomes after Sinus Surgery in Allergic Fungal Rhinosinusitis versus Nonfungal Chronic Rhinosinusitis

Abstract: Patients with AFRS experienced a more-prolonged QoL benefit from surgical and targeted medical intervention compared with those with CRSsNP, which may reflect the severity of inflammation that they presented with compared with other CRS subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…As demonstrated by Bewick et al the significantly higher Lund‐Mackay scores and number of total previous surgeries in this group support these findings . It has been reported that AFRS patients experience the most significant improvement in quality‐of‐life post‐surgery compared to other subgroups, which may reflect more aggressive initial disease and a more specialised level of surgical/medical care . These patients often necessitate early referral to tertiary centres, where they are more likely to be originally operated on by more experienced surgeons, including those with fellowship training.…”
Section: Discussionsupporting
confidence: 66%
“…As demonstrated by Bewick et al the significantly higher Lund‐Mackay scores and number of total previous surgeries in this group support these findings . It has been reported that AFRS patients experience the most significant improvement in quality‐of‐life post‐surgery compared to other subgroups, which may reflect more aggressive initial disease and a more specialised level of surgical/medical care . These patients often necessitate early referral to tertiary centres, where they are more likely to be originally operated on by more experienced surgeons, including those with fellowship training.…”
Section: Discussionsupporting
confidence: 66%
“…A total of 31 studies were considered to be duplicates from the same cohort, and an additional 53 failed to meet inclusion/exclusion criteria. The final study list included 40 unique patient cohorts published from 2008 to 2016 and representing institutions from North America (n = 14), Europe (n = 12), Middle East (n = 6), Australia (n = 3), Asia (n = 3), and South America (n = 2) . The majority of studies were prospective observational cohorts (n =2 3), with the remainder being surgical arms from randomized clinical trials (n = 7), retrospective cohorts (n = 7), or case‐control studies (n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…Five RCTs [14][15][16][17][18] and 25 RWE studies 65 reported mean baseline SNOT-22 scores in the moderate range. Five RCTs [19][20][21][22][23] and 17 RWE studies [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] reported severe mean baseline SNOT-22 scores. These findings were consistent with the treatment plan for CRSwNP provided by Fokkens et al 92 , which recommended surgery as treatment for patients with more severe symptoms or with polyps that are recalcitrant to medical management.…”
Section: Stratification Of Snot-22 Scores Prior To Surgerymentioning
confidence: 99%